The effect of board characteristics and audit committee characteristics on audit quality - Dheyaa Zamil Khudhair; Firas Khudhair Abbas Al-Zubaidi; Ali Abdulhussein Raji (Management Science Letters, 2019)
The issues of audit quality and audit committee have received huge consideration from the auditing profession, the general public population and the government controllers particularly after the prominent corporate outrages in firms like Enron, Global Crossing, Tyco, and WorldCom. These concerns discourage investors to invest in foreign and local businesses. The primary objective of the current study is to explore the impact of internal and external governance mechanisms such as board size, audit committee independence, audit committee expertise, and audit committee meetings on the quality of audit in selected firms. The study is carried out on a sample of Iraqi non-financial firms. The dependent variable is the audit quality measured as a dummy variable and it receives 1 if a firm receives audit services of big five auditing firms and zero, otherwise. To achieve the research objectives the study uses logit regression technique. The results indicate that there was a positive relationship between audit quality and the percentage of non-executive directors in the audit committee. The findings of the current study will be helpful for policymakers, researchers, accountants, financial experts, and audit practitioners in understanding the importance of the concept of audit quality and the key factors which affect the audit quality of any non-financial firms in Iraq.